The effect of cable fixation on union time in subtrochanteric femur fractures treated with cephalomedullary nailing - Fatih İlker Can; Emre Gültaç; Rabia Mihriban Kılınç; Cem Yalın Kılınç (Northwestern Medical Journal)
Aim: This study aimed to examine the effect of cable cerclage on reduction quality and union time in patients treated with cephalomedullary nails for subtrochanteric fractures.